ON THE INFLUENCE OF CAPITAL EXPENDITURE AND IMPLICIT PRICE DEFLATOR ON ECONOMIC GROWTH IN NIGERIA BETWEEN 2001 – 2020 - Abdulazeez, Sikiru A. (FUDMA JOURNAL OF SCIENCES, 2022)
Capital expenditure involves spending on assets. It has a lasting impact on the economy and helps provide a more efficient, productive economy. There is the need to examine the impact of government capital expenditure and implicit price deflator on economic growth in Nigeria. The data used is secondary in nature from Nigeria Bureau of Statistics. The statistical package used is SPPS Version 23. The objectives of this research work includes the determination of a model for predicting the growth of the GDP, to authenticate and validate the model for use and finally to predict the GDP given the revenue and implicit price deflator (IPD). From the analysis on multiple regression, it was observed that the p
Keywords: Goss Domestic Product (GDP), Capital Expenditure, Economic Growth, Price Deflator, Inflation, Deflation